Dampak Merek, Palayanan dan Proses dalam Sharia Marketing Value serta Socially Responsible Investment terhadap Citra Perusahaan dan Keputusan Investasi (Survei pada Investor Divisi Syariah PT XYZ, Jakarta) - Bafadhal, Aniesa Samira; ., Suharyono; Kumadji, Srikandi (Universitas Brawijaya, Indonesia, 2012)
The fragility of the capitalist economic system and the increasing competition in the capital markets make sharia securities firms need to implement competitive and market-oriented marketing strategiesbut still consider ethical investments, socially and in accordance with the principles of sharia through the implementation of sharia marketing strategies. This study aimed to test the marketing concept based onthe paradigm or Shariah Marketing Value consisting of Sharia Brand, Sharia Services, Sharia Process and evaluate the implementation of Socially Responsible Investment, which are assuwed to attect CompanyImage and the Investment Decision of investors. The population of this study is Sharia Division investors in PT.XYZ, Jakarta at 2011. The results of the data analysis by using Partial Least Square (PLS) are: 1) ShariaBrand, Sharia Process and Socially Responsible Investment partially significantly effect on the Company's Image. 2) Sharia Brand, Sharia Services and Socially Responsible Investment partially significantly attectInvesting Decisions. 3) Sharia Service does not affect significantly Company Image. 4) Sharia Process does not significantly affect to Invest rent Decision. Based on these results, it can be concluded that the professionalismand the principle of Shariah Islamic that offered by Sharia Marketing Value have been able to attract sharia capital market investors in Indonesia, especially on the Sharia Division, so that the consumersare not only dominated by investors with emotional and spiritual mindset but also rational investor (conventional investor). In addition, investors are considered to be ready to use the Socially Responsible Investment as a standard approach for their investment.